Bagaimana Reaksi Ketidaktepatan Waktu Pelaporan Keuangan yang Dipengaruhi Komponen-Komponennya : Studi Empiris di BEI Periode 2019-2023 - Dea Auliya Raafiatus Sholiha; Diyah Probowulan; Moh. Halim (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to analyzes how the effect of component or variable profitability, age companny, accounting firmm reputation, and public ownership on the untimeliness financial reporting for the 2019-2023 period in BEI. This research using purposive sampling method with 200 companny tottal sample of research. The research is quantitative strategies using causal comporative with logistic regression analyzes as analyzes technique. The results of this research prove that profitability have a significant negative effect on untimeliness financial reporting, contrast with age companny, accounting firm reputation, and public ownership has no effect on untimeliness financial reporting.